Penatalaksanaan Fisioterapi Pada Post Fraktur Metacarpal III Dekstra Di RSU 'Aisyiah Ponorogo - Firdiansyah, Ockta, Agus Widodo, S.Fis., M.Fis (2014)
Background: Definition of fracture according to Price and Wilson (2006) is a broken bone, usually aused by trauma or physical exertion. Meanwhile, according to Reeves, Roux and Lockhart (2001) each fracture is a crack or fracture in the bone intact. As for the problem that will arise both in the form of physical capacity such: the absence of pain in right fingers hand, decrease in range of motion, decrease muscle strength right fingers hand and problem of functional ability. To know how big the problem that arise necessary to check, eg for pain with VDS, decrease in range of motion with goneometer, muscle strength with MMT and functional ability with direct interview. In addressing the issue of exercise modalities can be obtained a reduction of pain, increase range of motion, increase muscle strength and reduced interference for functional activity. Methods: Writing this research uses the case study method with the implementation of therapy six times. Results: The results after treatment carried six times is as follows: silent pain of T1 = 1 and T6 = 0, tenderness of T1 = 4 and T6 = 2, painful motion of T1 = 3 and T6 = 1. ROM Active Metacarpophalangeal T1 = S: 5-0-35 be T6 = S: 15-0-70. ROM Active Interphalangeal Proximal T1 = S: 5-0-70 be T6 = S: 5-0-90. For the functional ability of patient has increased proved by patient wrting ability. Conclusion: In reducing the pain and the problems that arise with physiotherapy modalities Exercise therapy can reduce pain and problems experienced by the patient. With the provision of exercise therapy modalities are expected pain, edema, decreased LGS, decreased muscle strength and decreased physical ability and functional capacity can be overcome so that the patient can move back as before.